Functional dairy food seen as potential remedy to cancer and diabetes - Siti Nurfarmy, Ibrahim (2019)
A team of researchers from the Faculty of Industrial Science & Technology (FSTI) at Universiti Malaysia Pahang (UMP) – comprising lecturers and undergraduates – has embarked on a study of possible remedy for cancer and diabetes via the development of functional dairy food.